An??lise de Desempenho de Rede Cooperativa NOMA Incremental Full Duplex - Semedo, Elig??rio Milton Da Costa (2024)
A full-duplex incremental cooperative non-orthogonal multiple access (FD-ICN) scheme is proposed for a two user downlink network. NOMA-based incremental co operative communication is important to meet the specific demands and challenges of 5G and 6G technologies. It offers improved user reliability and spectral efficiency, especially when combined with full-duplex technologies. Based on a pilot signal from the far user, the base station decides between transmitting in direct transmission mode or using cooperation via the near user. The proposed scheme is evaluated in terms of the pair outage probability, in order to guarantee a feasible service for both users. Furthermore, the interruption probability is evaluated considering both perfect and im perfect SIC, in addition to user channel conditions U2. The results show that the propo sed scheme presents better performance in terms of outage probability, when compared with the half-duplex incremental cooperative non-orthogonal multiple access scheme as well as with the conventional non-orthogonal multiple access scheme. Keyords: Non-ortogonal multiple access, Incremental retransmission, Full-duplex